Kontribusi dewan pengawas syariah terhadap stabilitas dan integritas keuangan bank syariah - Devi, Haura Awalin Nurista (Maliki Interdisciplinary Journal, 2025)
The Sharia Supervisory Board (SSB) plays a central role in ensuring that Islamic banks operate in compliance with Islamic legal principles. This article aims to analyze the SSB's contribution to the financial stability and integrity of Islamic banks using a descriptive qualitative approach based on literature review. The findings indicate that the SSB contributes to financial stability by supervising sharia compliance risks, validating contracts, and reinforcing governance structures. It also safeguards financial integrity through improved transparency, accountability, and prevention of unethical practices. However, the effectiveness of the SSB remains challenged by limited independence and restricted access to internal information. Therefore, institutional strengthening of the SSB is needed to optimize its role in ensuring the sustainability of the Islamic banking system.